Sustainability, energy and architecture : case studies in realizing green buildings - Sayigh, A. A. M., 1939- (Oxford, UK : Academic Press, 2014)
Addresses what constitutes a sustainable building, suggesting bases for benchmarks, and explains the most important techniques and tools available to engineers and architects exploring green building technologies.
-- Table of Contents Copyright Preface Authors$1 (BBiographys Chapter 1. Dutch Efforts Towards a Sustainable Built Environment Abstract 1.1 Introduction 1.2 Passive Houses 1.3 Types of Case Studies 1.4 The Veldhuizerschool Ede 1.5 Christiaan Huygens College: an Energy Plus School 1.6 Conventional Dutch Building Design 1.7 Energy Saving Techniques 1.8 Novel Design and Examples 1.9 The TNT Green Office 1.10 Sustainability 1.11 Diverse Sustainability Measures 1.12 Results of GreenCalc+ and LEED Assessment References t t 2.5 Conclusion Chapter 3. Sustainable Construction Materials 3.1 Introduction 3.2 Demand for Construction Materials 3.3 Material Resources 3.4 Renewable Materials 3.5 Recycled Materials 3.6 Life Cycle Analysis 3.7 Embodied Energy 3.8 Gross Energy Requirement 3.9 Process Energy Requirement 3.10 Embodied Carbon 3.11 Natural Building Materials 3.12 Short Rotation Renewable Materials 3.13 Summary References Chapter 4. The Sustainable Corporate Image and Renewables: From Technique to the Sensory Experience Abstract 4.1 Introduction 4.2 Sustainable Innovation, or the Tried and Tested 4.3 The 20th Century, the Corporate Image and Sustainability 4.4 The Techno-Centric Sustainable Building in the 21st Century 4.5 The Sustainable Working Shed, Lion House, Alnwick, Northumberland, UK 4.6 Experiencing Renewables in Building Skins 4.7 The Responsive Skin and Corporate Image 4.8 Increasing Facade Layers: Double Skin Facades as a Passive Measure and a Cultural Message 4.9 Sustainability as Haptic Experience Conclusions References Chapter 5. Residential Deep Energy Retrofits in Cold Climates Abstract 5.1 Introduction 5.2 Building Materials and Assemblies 5.3 Ventilation and Air Movement 5.4 Case Studies Chapter 6. Sustainable Building for a Green and an Efficient Built Environment: New and Existing Case Studies in Dubai Abstract 6.1 Introduction 6.2 Climate Change: Cities and Buildings 6.3 Importance of Sustainable/Green Building 6.4 Sustainability Regulations and Laws Contributing to Carbon Emissions Reduction 6.5 Taxonomy of a Sustainable Building 6.6 Green Buildings in Dubai, UAE 6.7 Conclusions References Suggested Reading Chapter 7. The LED Lighting Revolution Abstract 7.1 Introduction 7.2 From LED Chips to Fixtures 7.3 Optics 7.4 Fixture Body 7.5 Advantages and Features 7.6 Comparisons with Traditional Lighting 7.7 Architectural/General Illumination Applications 7.8 Case Studies 7.9 Future/Novel Designs Possible with LEDs 7.10 Conclusions References Chapter 8. Minimum Energy Housing in Cuba Abstract 8.1 Introduction 8.2 Life Cycle and Sustainable Buildings 8.3 Design Strategies in Warm and Humid Climates 8.4 The Urban Microclimate 8.5 Vernacular Architecture in Cuba 8.6 Modern Architecture in Cuba 8.7 Present and Future 8.8 Final Remarks Chapter 9. Daylighting Abstract 9.1 Introduction 9.2 Characteristics and Availability 9.3 Photometric Units 9.4 Colors 9.5 Daylight Availability 9.6 Performance of Daylighting 9.7 Comfort and Health 9.8 Visual Performance 9.9 Daylight Factor 9.10 Thermal Comfort and Energy Use 9.11 Daylighting Design 9.12 Daylighting Systems and Solar Control 9.13 Energy Saving and Daylight Responsive Controls 9.14 Design Tools References Chapter 10. Vernacular Tower Architecture of Sana$1 (Ba: Theory and Method for Deriving Sustainable Design Guideliness Abstract 10.1 Introduction 10.2 Background 10.3 Theoretical Model for Sustainable Architecture 10.4 Analysis 10.5 Conclusion References Appendix A Sustainable Design Guidelines Derived From Response of Architectural Form and Space to Climatic and Functional Factors Appendix B A Comparison between a Vertical Form and a Horizontal Form Chapter 11. Sustainable Buildings in Mediterranean Area Abstract 11.1 Abitare Mediterraneo Project 11.2 EULEB t t t Abstract 12.1 Introduction 12.2 The Building$1 (Bs Energy Systems and Buildings in Energy Systemss 12.3 Energy Use in Swedish Building Sector 12.4 Energy Use in Residential Buildings 12.5 New Technologies that Make Buildings more Energy-Efficient and Environmentally Sound 12.6 Action Plans and Energy Policies to Achieve Energy-Efficient Buildings 12.7 Building and the Health of Occupants 12.8 Some Examples of Low-Energy Buildings in Sweden t References Chapter 13. Key Characteristics of Top Performing Sustainable Buildings from the Perspective of the Users Abstract Acknowledgments 13.1 Introduction 13.2 The Buildings and their Users 13.3 Survey Methodology and Analytical Procedures 13.4 Design Features of Buildings with High Summary Indices 13.5 Key Characteristics and Common Features of these Sustainable Buildings References Appendix Calculation of Indices Chapter 14. Sustainable Buildings and their Relationship with Humans and Nature: Lessons from the Past Abstract Acknowledgments 14.1 Background and Present Situation 14.2 Traditional Architecture; The Outcome of a Complex Thinking System 14.3 Traditional Architecture and Adaptive Response to Climate 14.4 Wind Catcher/Tower 14.5 Spatial Organization: A Means to Adapt to Culture and Climate 14.6 Conclusion References and further reading Chapter 15. Architectural Buildings in Romania 15.1 One Family House in Burlusi Ciofringeni, Arges County, Romania t 15.6 Conclusions References Chapter 16. Sustainable Architecture in Africa Abstract 16.1 Introduction 16.2 Bioclimatic Project: General Guidelines 16.3 Climatic Context 16.4 Building Location, Form and Orientation 16.5 Shading 16.6 Envelope Coatings 16.7 Insulation 16.8 Window Size and Glazing Type 16.9 Natural Ventilation 16.10 Thermal Mass 16.11 Evaporative Cooling 16.12 Control of Internal Gains 16.13 The Use of Environmental Controls 16.14 Passive Design and Thermal Comfort Criteria t
Includes bibliographical references and index.
Keywords: Sustainable architecture; Sustainable buildings -- Design and construction; Sustainable architecture -- Case studies; Sustainable buildings -- Design and construction -- Case studies